Trypanosoma of subgenus Herpetosoma Doflein, 1901 in Proechimys iheringi Thomas, 1911 captured alive in São Paulo State, Brazil - Tolezano, José Eduardo (1984)
The blood of wild rodents captured alive in the field station of Casa Grande, municipality of Salesópolís, State of São Paulo was examined for hemoparasites. Trypanosomas of the subgenus Herpetosoma were discovered in the blood of 4 specimens of Proechimsis iherinçi, The parasites showed an average size of 21.7 J.Lm and an average nuclear index equivalent to 1.9. Attempts to cultivate the trypanosomas in NNN, Lit and Ducrey media failed. However, when Ducrey medium was added 2% of blood of Proechim.us 'iheringi there was abundant growth of mastigotes. Inoculation of Mus mUBculus, Akodon sp., Oryzomys sp. and Cricetus auratus were negative; however, inoculation of laboratory-born and reared Proechimys iheringi was successful and there was circulation of the parasite in the blood.It is suggested that the parasites isolated belong to a new species considering the behavior and specificity of the subgenus Herpetosoma to vertebrate hosts and the characteristics of the ísolates.